Freedom and its Betrayal Six Enemies of Human Liberty - Barnes, John Arthur (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
This volume is the second impression of the original work undertaken by Henry Hardy an executive of Isaiah Berlin’s literary trustees. The book comprises an Introduction and six chapters each explaining the philosophy and application by of a notable philosopher who was not in favour of the liberal theories and practices we enjoy today. The contents will be of special interest to students of philosophy and ethics.